2011
DOI: 10.1111/j.1582-4934.2010.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of aldehyde dehydrogenase 2 Glu504lys polymorphism in acute coronary syndrome

Abstract: This study aimed to investigate the association of the aldehyde dehydrogenase 2 (ALDH2) Glu504Lys polymorphism, which exists in 30–50% of East Asians, and risk of acute coronary syndrome (ACS). We enrolled 1092 unrelated Han Chinese, including 546 with ACS and 546 age- and sex-matched controls. Subjects with ALDH2 mutant genotypes showed significantly higher ACS than did controls (46.7% versus 31.9%, P < 0.001). Logistic regression analysis revealed the ALDH2 mutant independently associated with ACS (odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 25 publications
11
55
0
Order By: Relevance
“…Our group found that carriers of the ALDH2 *504Lys allele drink significantly less than carriers of the wild-type ALDH2 (Xu et al 2011), which was consistent with other studies in Chinese populations (Muramatsu et al 1995;Ding et al 2008). Additionally, when alcohol consumption was incorporated into the regression analysis model as an independent variable, the correlation between ALDH2 *504Lys allele and ACS decreased but was still significant (Xu et al 2011).…”
Section: Underlying Mechanisms Of * 504lys Allele Influencing Cadsupporting
confidence: 91%
See 3 more Smart Citations
“…Our group found that carriers of the ALDH2 *504Lys allele drink significantly less than carriers of the wild-type ALDH2 (Xu et al 2011), which was consistent with other studies in Chinese populations (Muramatsu et al 1995;Ding et al 2008). Additionally, when alcohol consumption was incorporated into the regression analysis model as an independent variable, the correlation between ALDH2 *504Lys allele and ACS decreased but was still significant (Xu et al 2011).…”
Section: Underlying Mechanisms Of * 504lys Allele Influencing Cadsupporting
confidence: 91%
“…Additionally, when alcohol consumption was incorporated into the regression analysis model as an independent variable, the correlation between ALDH2 *504Lys allele and ACS decreased but was still significant (Xu et al 2011). Studies conducted by Japanese and South Korean scholars reached similar conclusions (Takagi et al 2002;Jo et al 2007).…”
Section: Underlying Mechanisms Of * 504lys Allele Influencing Cadmentioning
confidence: 58%
See 2 more Smart Citations
“…Acute coronary syndrome includes physiological conditions such as elevated blood pressure, heart attacks, and hypertension. Several studies have shown that the ALDH2*2 mutation is an independent risk factor for ACS [63][64][65][66]. More specifically, other studies have confirmed that an ALDH2 mutation is a strong risk factor for symptoms of elevated blood pressure and hypertension in males who consume high amounts of alcohol [67,68].…”
Section: Diseases Associated With the Inheritance Of Aldh2*2mentioning
confidence: 98%